APLIKASI PEMBELAJARAN MATEMATIKA BERBASIS WEB PADA SMPN 9 KOTO XI TARUSAN - Surianda, Venia Maria; Dahri, Nuraeni (JENTIK, 2024)
The web-based mathematics learning application at SMPN 9 Koto XI Tarusan aims to make the teaching and learning process more effective and efficient so that the time required is less than the conventional teaching and learning process. The data collection methods used are primary and secondary data, the system development method used is SDLC with UML (Unified Modeling Language) system design tools and uses a computerized system using black techniques. This learning application produces output in the form of information on student learning outcomes accurately and in a timely manner. This learning application apart from producing an effective and efficient teaching and learning process also produces more interesting learning information, namely by having a learning method using multimedia learning media compared to conventional learning.